Physical characteristics and nutritional value of stored mulberry (Morus alba) mixed with corn forage. - Boschini-Figueroa, Carlos (2003)
Mulberry foliage and corn, harvested respectively after 120and 135 days, were ensilaged (chopped and mixed in ratios of100:0, 75:25, 50:50, 25:75 and 0:100 as dry material). Theconcentration of soluble carbohydrates was uniform at 10%in all the treatments by adding molasses. The fermentationperiod was 90 days. The compacted mulberry forage (the100:0 ratio) had a density of 693 kg/m3 and that of the cornforage (the 0:100 ratio) was 541 kg/m3, indicating markedinitial differences (p≤ 0.01) between them. At the end of theexperimental period, the stored material had densities rangingbetween 750 and 556 kg/m3, with intermediate values(p≤0.01) as the mulberry proportion was reduced in eachmixture. Loss of dry material was found among treatments(p≤0.01) with 6.8 kg/m3 and 18.3 kg/m3. The organolepticcharacteristics evaluation had ratings from very good toexcellent in the mixtures with ratios of 75:50, 50:50, 25:75and 0:100, but not in the mulberry forage (100:0) which hasa slight ammonia odor. The concentration of dry matter in thefresh material was higher than that found in the storedmaterial (p≤0.05). The concentration of crude protein amongthe mixtures was clearly differentiated (p≤0.01), in thebeginning as well as at the end of the fermentation period. Asimilar condition was observed in the concentration of neutraldetergent fiber and total ash.